Interferon-based chemoradiation followed by gemcitabine for resected pancreatic adenocarcinoma: long-term follow-up. Issue 5 (May 2017) - Ohman, Kerri A.; Liu, Jingxia; Linehan, David C.; Tan, Marcus C.; Tan, Benjamin R.; Fields, Ryan C.; Strasberg, Steven M.; Hawkins, William G.
Abstract: To report long-term follow up of a phase II, single-arm trial of resectable pancreatic ductal adenocarcinoma (PDAC) treated with adjuvant interferon-based chemoradiation followed by gemcitabine to determine survival, recurrence, and complications. Methods: From 2002 to 2005, 53 patients with PDAC underwent pancreaticoduodenectomy and received adjuvant interferon-based chemoradiation consisting of external-beam irradiation and simultaneous 3-drug chemotherapy of continuous daily 5-fluorouracil infusion, weekly intravenous bolus cisplatin, and subcutaneous interferon-α, followed by two months of weekly intravenous gemcitabine. Results: Actual overall survival for the 5- and 10-year periods were 26% and 10%, respectively, with a median overall survival of 25 months (95% CI: 16.4–38.5). Adverse prognostic factors on multivariate analysis were positive tumor margin ( p  < 0.035), lymphovascular invasion ( p  < 0.015), and perineural invasion ( p  < 0.026). Median time to recurrence was 11 months. Positive tumor margin was associated with lymph node involvement ( p  < 0.005), portal vein resection ( p  < 0.038), and metastases ( p  < 0.018). Late complications were frequent and predominated by gastrointestinal and infectious complications. Conclusions: Adjuvant interferon-based chemoradiation for PDAC improves long-term survival compared to standard therapy. However, recurrence rates and long-term complications remain high, thus further studies are indicated to assess patient characteristics that indicate a favorable treatment profile.